Análise da integridade do esmalte dentário pós-remoção do remanescente residual ortodôntico - Degrazia, Felipe Weidenbach (2012)
The integrity of enamel has attracted attention of researches. Structural modifications could lead to higher bacterial retention and light reflection changes, and there the need to restore dental enamel to conditions closer to its initial state after bonding and debonding orthodontic procedures. The aim of this work was to determine and compare roughness parameters and appearance of the enamel after remnant adhesive removal, and evaluate time required for the different methods. Sixty one healthy human premolars extracted for orthodontic reasons were used, and 60 of them were examined with a profilometry analysis of surface roughness into two axes, horizontal (X) and vertical (Y). Performed this step, the specimens were submitted to bracket bonding procedure with phosphoric acid conditioning, washed and dried, a thin layer of adhesive system and light curing. After bracket debonding the specimens were randomly divided by removal method into: group 1 (control) - tungsten carbide tip (5 blades), at high speed, group 2 - tungsten carbide tip (30 blades), at high speed, and group 3 - a diamond chemical vapor deposition with ultrasound. The removal time of each remnant was recorded in seconds, and all procedure occurred under light reflector, simulating the clinical management. Thus, the samples were again submitted to profilometry analysis. Two images were obtained with 20x and 100x increase in scanning electron microscopy (SEM) of one specimen per group, chosen randomly, and one specimen that had not had its roughness evaluated, forming the Healthy group. The images were scored by two calibrated observers, such as: score 0 - perfect surface, score 1 - acceptable surface, score 2 - imperfect surface, and score 3 - unacceptable surface. Comparing roughness with intact enamel, generally, in X axis, all roughness parameters increased after the three methods, with exception of Rku and Rsk parameters. And generally, in Y axis, Ra, Rz, and Rz parameters decreased after removal in groups 1 and 2 and increased after group 3. Comparing each group after removal, in X axis, the first group showed the lowest roughness values and group 3 the largest and, in Y axis, the second group had the lowest values of Ra, Rq and Rz and group 3 the lowest values of Rku and Rsk parameters. The images were classified as Healthy Group - score 0, Group 1 - score 1, Group 2 - score 2 and Group 3 score 3. A significant increase in time removal occurred in group 1 relative to group 3. Thus, no cleanup procedures restore the enamel roughness to its original surface in all groups. The slowest procedure was performed with tungsten carbide 5 blades group.